Confianza en un sistema de Gestión de seguridad y la accidentabilidad en proyectos de construcción - Noboa de la Torre, Carlos Andrés (2018)
The construction industry is one of the main sectors of the national economy, but at the same time, it is one of the most dangerous sectors since it has one of the highest rates of work accidents. Dekker establishes a complex system which identifies trust as the mechanization of processes in which the cause of work accidents is not taken into account. The purpose of the present investigation was to establish whether there is a correlation between the trust embodied in the "Occupational Health and Safety Management System" and the accident rate in construction projects. To measure these variables, a matrix was developed that allowed establishing the confidence index, a survey that helped determine the accident rate. The data taken in 14 construction projects revealed 6 projects with strict control and follow-up regarding the compliance of the safety management system, and 8 projects without said control. A Spearman nonparametric statistical method was used for the correlation of the study variables, which rendered the following result: There is a correlation between these study variables in the projects where there is no control or monitoring of the security management system, as opposed to the projects where there is control related to compliance, where no correlation was found. An increase in the sample is still pending, focusing on a single branch of civil engineering to verify the correlation between the study variables.